Shooting Accuracy in Junior High School Football Extracurricular Activities: Study Examines How Leg Muscle Power And Ankle Coordination Relate - Natalius Hulu; Carlan Septianus Samatohu Gulo; Ade Efriansyah Lubis (Joska: Jurnal Isori Kampar, 2024)
Objectives: Shooting accuracy represents a fundamental skill in football performance, particularly critical during adolescent development in junior high school athletes. The biomechanical factors influencing shooting precision remain inadequately understood in this population. This research investigated the relationship between leg muscle power, ankle coordination, and shooting accuracy in junior high school football players participating in extracurricular activities. Methods: A cross-sectional study was conducted with 45 male junior high school football players (aged 13-15 years) from three schools in North Sumatra, Indonesia. Leg muscle power was assessed using vertical jump tests, ankle coordination through dynamic balance assessments, and shooting accuracy via standardized target shooting protocols. Pearson correlation analysis and multiple regression modeling were employed to examine relationships between variables. Results: Significant positive correlations were found between leg muscle power and shooting accuracy (r = 0.687, p < 0.001) and ankle coordination and shooting accuracy (r = 0.623, p < 0.001). Multiple regression analysis revealed that leg muscle power and ankle coordination collectively explained 58.4% of the variance in shooting accuracy (R² = 0.584, p < 0.001). Conclusion: Leg muscle power and ankle coordination are significant predictors of shooting accuracy in junior high school football players. These findings suggest that training programs should incorporate specific exercises targeting these biomechanical components to enhance shooting performance.